ANALISIS KARAKTER PENGGUNA BLACKBERRY MESSENGER DALAM MEMENUHI KEBUTUHAN INTERAKSI SOSIAL (STUDI PADA PENGGUNA BLACKBERRY MESSENGER) - Istiana Indri (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
ABSTRACT This study aims to determine the character of the social media Blackberry Messenger users. Using a qualitative research method by using purposive sampling. Subject or informants amounted to 6, where they are active users of social media Blackberry Messenger. Data collected through the process of documentation and observation. The theory used is the theory of personality types Hippocrates-Galenus stating that human beings can be classified into 4 characters namely sanguine, Choleric, Melancholic, plegmatis. The analysis was conducted through two stages. The first stage is done by matching the informant status of each account following character traits. The second stage is done by giving a matter of choice personality tests a, b, c, d. each option shall contain character traits sanguine, b load the character traits plegmatis, c contains character traits melancholic, d load plegmatis character traits. The results show from 6 subjects in the study 1 has sanguine character. Characteristic of the display that is as simple character that is the hallmark sanguine, one of the next six koleris character. Characteristics that are envisaged as an optimistic person where it is characteristic of the character choleric. 2 of the next six melancholic character as BBM users are poetic and melancholic 2 others plegmatis character with the character description fun and simple. Keywords: Character, Blackberry Messenger users, Sanguine, Choleric, Melancholic, plegmatis.